(untitled) (Proceedings of Southern Federal University. Philology, 2016)
Tsebrovskaya Tatyana Alexandrovna – lecturer of the department of foreign languages No3. Institute of Foreign Philology of Taurida Academy (structural department) of V.I. Vernadsky Crimean Federal University. Abstract. The article studies word formation of the derogatory marked ethnonyms (DME) of the Canadian, Australian and New Zealand English Language. DME are classified according to the method of word formation, the type of semantic transfer and deliberate phonetic distortion. Selection of the analyzed units is made out of such lexicographical sources as online dictionary of colloquial vocabulary Urban Dictionary, online dictionary Oxford English Dictionary, Merriam-Webster Online: Dictionary and Thesaurus, ABBYY Lingvo, The Free Dictionary, Dictionary.com, electronic databases The Racial slur Database and Hatebase, lists of ethnonyms from online resources canadaka.com, fact-index.com and other sources of factual materials. The urgent character of the given article is caused by lack of scientific study of the ways of word formation of DME, particularly, the units of Canadian, Australian and New Zealand English. Separation of the criteria of their description and division into groups are considered to be important. The aim is to justify the linguistic phenomenon of DME through determining their structural and semantic characteristics in Canadian, Australian and New Zealand English. Achievement of the aim requires solving the following problems: 1) to identify the structural and semantic parameters of formation of DME; 2) to improve the structural and semantic classification of A.I. Hryshchenko for Canadian, Australian and New Zealand English. Key words: derogatory marked ethnonym, structural-semantic classification, word formation, semantic transfer, phonetic distortion, Canadian English, Australian English, New Zealand English.